Incidence and characteristics of pregnancy‐related death across ten low‐ and middle‐income geographical regions: secondary analysis of a cluster randomised controlled trial. (2nd June 2020) - Vousden, N; Holmes, E; Seed, PT; Gidiri, MF; Goudar, S; Sandall, J; Chinkoyo, S; Kumsa, LY; Brown, A; Charantimath, U; Bellad, M; Nakimuli, A; et al.
Abstract : Objective: The aim of this article is to describe the incidence and characteristics of pregnancy‐related death in low‐ and middle‐resource settings, in relation to the availability of key obstetric resources. Design: This is a secondary analysis of a stepped‐wedge cluster randomised controlled trial. Setting: This trial was undertaken at ten sites across eight low‐ and middle‐income countries in sub‐Saharan Africa, India and Haiti. Population: Institutional‐level consent was obtained and all women presenting for maternity care were eligible for inclusion. Methods: Pregnancy‐related deaths were collected prospectively from routine data sources and active case searching. Main outcome measures: Pregnancy‐related death, place, timing and age of maternal death, and neonatal outcomes in women with this outcome. Results: Over 20 months, in 536 233 deliveries there were 998 maternal deaths (18.6/10 000, range 28/10 000–630/10 000). The leading causes of death were obstetric haemorrhage (36.0%, n  = 359), hypertensive disorders of pregnancy (20.6%, n  = 206), sepsis (14.1%, n  = 141) and other (26.5%, n  = 264). Approximately a quarter of deaths occurred prior to delivery (28.4%, n  = 283), 35.7% ( n  = 356) occurred on the day of delivery and 35.9% ( n  = 359) occurred after delivery. Half of maternal deaths (50.6%; n  = 505) occurred in women aged 20–29 years, 10.3% ( n  = 103) occurred in women aged under 20 years, 34.5% ( n  = 344) occurred in women aged 30–39 years and 4.6% ( n  = 46) occurred in women aged ≥40 years. There was no measured association between the availability of key obstetric resources and the rate of pregnancy‐related death. Conclusions: The large variation in the rate of pregnancy‐related death, irrespective of resource availability, emphasises that inequality and inequity in health care persists. Tweetable abstract: Inequality and inequity in pregnancy‐related death persists globally, irrespective of resource availability. Tweetable abstract: Inequality and inequity in pregnancy‐related death persists globally, irrespective of resource availability.